A HAZOP Teaching Module and Verification Strategy for the Chemical Engineering Capstone Subject - Scholes, Colin A (Chemical engineering education, 2023)
A teaching module for HAZOPs is presented here that was included in the capstone subject. The module included a lecture, class exercise and an advisors' led workshop. Some students undertake HAZOPs individually, representing academic misconduct. A verification strategy, based on Zipf's law, is presented that analyses word frequency and key words presented in the HAZOP reporting tables, to determine if students had undertaken group work. The presented examples demonstrate the effectiveness of this verification strategy.